Faktor-Faktor Yang Mempengaruhi Status Gizi Remaja Siswa/I Kelas X Dan Xi Di SMK Farmasi Bogor - Made Ditya Kusuma; Gusti Kumala Dewi (Jurnal Ilmu Kesehatan dan Gizi, 2024)
A person's nutritional status may be used as a gauge to illustrate how their body functions based on the foods they eat. There are five categories into which nutritional status can be categorized: less, less, good, more, and obese. A number of factors, including physical activity, snacking habits, and patterns of vegetable and fruit eating, might contribute to problems with nutritional status. To determine what elements affect the nutritional state of high school pupils in classes X and XI, a cross-sectional observational study design is used. The Bogor Pharmacy Vocational School was the location of the research. For this study, a sample of 101 people was selected using simple random selection as the sampling strategy. Nutritional status (BMI/U), fruit and vegetable consumption (FFQ interview), snacking habits (FFQ interview), and physical activity (PAQ-Q questionnaire) were used to gather data. A chi-square test was used for data analysis. The findings indicate that 65.3% of students at the Bogor Pharmacy Vocational School have adequate nutritional conditions. Additionally, the bivariate data demonstrate a substantial correlation (p = 0.020) between fruit and vegetable intake. snacking patterns on teenage nutritional status (p = 0.018). There is no statistically significant correlation (p = 0.1000) between teenage dietary status and physical activity.